Investigating the Role of Home Learning Environment in Shaping Children’s Literacy Development: A Comparative Analysis of Two Families in Rural India - Malo, Sanjib (Voices of Teachers and Teacher Educators, 2024)
‘Home learning environment’ refers to the learning activities occurring within the four walls of one’s house , encompassing both formal and informal values, beliefs, and attitudes shared between parents and children. Napoli and Purpura (2018) delineate this environment as comprising the home literacy environment (HLE) and the home numeracy environment (HNE), both of which significantly impact children’s literacy development. Through a qualitative research approach, this paper investigates the dynamics of the home learning environment and its influence on literacy development in children in the context of India. The findings underscore the pivotal roles of parenting practices and home learning environment in fostering essential competencies among young children. Furthermore, the study highlights a noticeable discrepancy between middle-class and lower middle-class families, making it imperative for community members, educators and NGOs to provide support tailored to the latter group’s needs.